Development application smartness help for the disabled blind with text and image - Putri, Anggi Erlina; Azizah, Nur; Jannah, Irradhiatul (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2023)
Blindness is a condition in which a person's sense of sight does not function either partially (low vision) or as a whole (total blindness). Physical limitations make it diffi cult for them to access information and knowledge in the form of books or other printed media. This study was aimed at developing application smartness help for the disabled blind with text and image. The research method (R&D) uses the waterfall model. The study was conducted at SLB-A YPPLB Payakumbuh with the results of the assessment of material experts 93.3%, and media experts 86.7% who stated that the Smartness Help application was